The influence of transport resiliency on community level food security - Hossain, Shahadat (My University, 2025)
Transportation systems play a vital role in linking urban communities to food sources, yet the resilience of transportation systems and how it influences local level food security is not well understood. When severe weather disrupts transportation, vulnerable populations encounter difficulties accessing nutritious food, exacerbating existing inequities in food security. Despite the recognition of these interconnections, prior research often analyzed transportation resilience and food security independently, with limited exploration of their intersection. This study addresses this critical research gap by examining how transportation network resilience impacts food accessibility during extreme weather events. We hypothesize that areas with more resilient transportation infrastructure maintain better food access during disruptions, but that this relationship varies across socioeconomic characteristics. We took the Kansas City Metropolitan Area as our case study and explored transport resilience and food security at the census block group level. Our methodology includes developing a Transportation Resiliency Index (TRI) incorporating measures of redundancy, mobility, and vulnerability. We paired this with mobile phone-based foot traffic data to food stores to create a Retail Food Activity Index (RFAI) that captures real-world mobility patterns rather than assuming local food accessibility based on distance to stores. We applied spatial regression models to evaluate how visitation to healthy food stores (as measured by RFAI) is influenced by transport resilience and distance to stores after controlling different socioeconomic variables. We developed this model for both normal weather conditions and a major snowstorm period. Our analysis reveals significant patterns in food store visitation during both normal and snowstorm conditions. Transportation resilience emerged as one of the most significant predictors across both scenarios, with its influence intensifying during disruptions caused by the snowstorm. Our model results also revealed stark socioeconomic disparities, with areas containing higher percentages of low-wage residents experiencing reduced food access, mirroring patterns of infrastructure inequality. These findings have significant implications for planning practice and policy. This study underscores the critical need to integrate transportation and food system planning to advance equity and resilience. This research provides a transferable methodology for identifying at-risk areas and a framework for developing targeted interventions to address food security at the local level.
Keywords: Transportation resilience; Food security; Community food access; Mobility data